2021
DOI: 10.1016/j.asmr.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Restoration of Bipolar Lesions Within the Patellofemoral Joint Delays Need for Arthroplasty: A Systematic Review of Rates of Failure

Abstract: The purpose of the present review is to systematically review the available literature for failure rates and complications of cartilage restoration of bipolar chondral defects in the patellofemoral (PF) joint to assess the ability to treat these lesions without arthroplasty. Methods: PubMed and MEDLINE databases were queried between 2000 to 2020 using the keywords "osteochondral" and "knee" and "microfracture," "autologous chondrocyte implantation (ACI)," or "transplantation." Patient selection included patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Gowd et al found that across all cartilage restoration treatments, the majority of patients did not require conversation to an arthroplasty at short- to long-term follow-up, and, even in the cases of those who did, the need for an arthroplasty was delayed 2.8 to 5.5 years. 4 5…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Gowd et al found that across all cartilage restoration treatments, the majority of patients did not require conversation to an arthroplasty at short- to long-term follow-up, and, even in the cases of those who did, the need for an arthroplasty was delayed 2.8 to 5.5 years. 4 5…”
Section: Tablementioning
confidence: 99%
“…Gowd et al found that across all cartilage restoration treatments, the majority of patients did not require conversation to an arthroplasty at short-to longterm follow-up, and, even in the cases of those who did, the need for an arthroplasty was delayed 2.8 to 5.5 years. 4,5 The available literature has clearly demonstrated that cartilage restoration procedures can be performed safely with minimal complication rates, and associated with substantial improvements in patients' pain and function. 6 Among athletes undergoing cartilage restoration procedures, relatively high rates of success with an overall return to preinjury level of sport rate of 66% have been observed.…”
mentioning
confidence: 99%